Laparoscopic choledochoduodenal anastomosis after bile duct injury in a patient with previous laparoscopic gastric bypass - Cuendis-Velázquez, Adolfo; Pérez-López, Francisco; Barlandas-Quintana, Erika; Bada-Yllán, Orlando; Ríos-Muñoz, Braulio (International Surgery Journal, 2021)
Bile duct injuries after laparoscopic cholecystectomy remain a major problem in gastrointestinal surgery. Twenty five to thirty percent of bariatric patients could develop gallstone disease. However, laparoscopic cholecystectomy in this group may result challenging due to the presence of a previous Roux-en-Y reconstruction. We documented the successful case of 66 year old female with story of non-supplemented laparoscopic gastric bypass, with subsequent injury of bile duct during laparoscopic cholecystectomy treated with a laparoscopic choledochoduodenal anastomosis. This technique offers an excellent alternative to solve highly complex cases in a single surgical time, allowing the patient to restore his original functionality prior to the biliary duct lesion.